Intermittence in irrigation management and nitrogen optimize yield and water use efficiency in baby lettuce - Pereira, Laércio da Silva [UNESP]; Saad, João C. C. [UNESP]; Cardoso, Antonio I. I. [UNESP]; Silva, Marcelo A. [UNESP]; Lima, Carlos J. G. S.; Silva, Everaldo M. (Instituto Nacional de Investigacion y Tecnologia Agraria y Alimentaria (INIA), 2023)
Aim of the study: To evaluate the influence of irrigation management strategies and nitrogen (N) on baby lettuce growth, yield, and water use efficiency in a protected environment. Area of study: Botucatu, SP, Brazil. Material and methods: The experiments were conducted in two consecutive cycles, and the treatments corresponded to the combination of irrigation management strategies with N doses. Irrigation strategies comprised 3 possibilities: continuous irrigation (Cont); intermittent irrigation with three irrigation pulses at one-hour intervals (Int1); and intermittent irrigation with irrigation depth split and applied at 7:00, 11:00, and 15:00 h (Int2). Two N doses were evaluated, 100 and 130 kg/ha of N, applied in daily fertigation according to the irrigation management strategies. Main results: Intermittent irrigation strategies (Int1 and Int2) promoted the highest vegetative growth, increased leaf water content, and increased total yield (49.55 and 55.30; 46.83 and 49.50 t/ha) and marketable yield (46.77 and 52.44; 45.11 and 47.17 t/ha) in the first and second cycles, respectively, in addition to optimizing water use efficiency. The N dose of 130 kg/ha increased the total yield (51.61 t/ha), marketable yield (48.98 t/ha), and water use efficiencies of total yield (53.60 kg/m³) and marketable yield (50.88 kg/m³) only in the first crop cycle. Research highlights: The use of intermittence in irrigation management proved to be more efficient in obtaining high yields and maximized the efficiency of use of water as a factor of production.
Keywords: drip irrigation; fertigation; Lactuca sativa L; pulse irrigation; vegetative growth